(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
This review emphasizes the significance of fenugreek and its extensive applications in the poultry industry. This information is obtained by providing an explanation of the plant’s description, classification, chemical composition, and active elements. Furthermore, it highlights the plant’s extensive therapeutic applications, such as its effectiveness as an anti-diabetic, anti-inflammatory, and anti-cancer agent. Additionally, the report examines contemporary methods of injecting eggs with fenugreek extract and analyzes the effects of this practice on the productivity, health, and physiological state of poultry. The promising role of fenugreek in improving poultry health and productivity sheds light on its importance for the poultry industry.